2002
DOI: 10.1258/002221502760132575
|View full text |Cite
|
Sign up to set email alerts
|

Effect of KTP laser on implants used in middle-ear surgery

Abstract: The present study is intended to explore the effects of the KTP laser on various types of implant, used in middle-ear surgery. A laboratory study was undertaken to evaluate the interaction between the KTP laser (KTP-532 Orion Laser, Laserscope, UK) and individual middle-ear implants. A variety of middle-ear implants were used: a silicone sheet, Teflon, hydroxylapatite, ionomeric cement, gold and titanium prostheses as well as gelfoam. Following exposure to the laser, these implants were studied by direct inspe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…The effect of laser energy on the piston is important and may influence the choice of surgical technique. Gerlinger et al 4 laser on different types of prostheses. Hydroxylapatite prostheses shattered when exposed to KTP laser energy.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of laser energy on the piston is important and may influence the choice of surgical technique. Gerlinger et al 4 laser on different types of prostheses. Hydroxylapatite prostheses shattered when exposed to KTP laser energy.…”
Section: Discussionmentioning
confidence: 99%
“…Wanamaker and Silverstein 3 and, more recently, Gerlinger et al 4 have examined the effect of the potassium-titanyl-phosphate (KTP) laser on middleear implants. Both studies showed that the KTP laser may damage fluoroplastic pistons, especially when blood was added to the surface of the piston.…”
Section: Introductionmentioning
confidence: 99%
“…Use of silicon implants in ossiculoplasty is rarely reported despite their enormous prospects [4]. The present study is an attempt to evaluate the feasibility, increase in hearing sensitivity, extrusion rate and cost effectiveness of silicon implants in middle ear reconstruction surgeries.…”
Section: Introductionmentioning
confidence: 99%
“…This may result in inadvertent laser hits on the prosthesis. Wannamaker and Silverstein 4 and Gerlinger et al 5 have studied the effect of KTP lasers on various materials and prostheses used in middle-ear surgery and Wannamaker and Silverstein 4 also examined the effects of the argon laser. Both groups reported that little damage occurred to stapes pistons unless blood was present on their surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Gerlinger et al 5 suggested that heat might be transmitted to the vestibule when a piston is hit by a laser pulse or pulses and that this might have undesirable effects. This would depend on the resultant temperature change.…”
Section: Introductionmentioning
confidence: 99%